Bipolar disorder and multiple sclerosis Transtorno bipolar e esclerose múltipla - Mariana Inés Ybarra; Marcos Aurélio Moreira; Carolina Reis Araújo; Marco Aurélio Lana-Peixoto; Antonio Lucio Teixeira (Arquivos de Neuro-Psiquiatria, 2007)
Bipolar disorder may be overrepresented in multiple sclerosis (MS) patients. Although research in this area is limited, studies assessing the nature of this association have focused on genetic aspects, adverse reaction to drugs and brain demyelinating lesions. Herein we report three patients with MS that also presented bipolar disorder. The coexistence of neurological and psychiatric symptoms in most MS relapses highlights the relevance of biological factors in the emergence of mood disorders in these patients. O transtorno bipolar do humor parece estar super-representado em pacientes com esclerose múltipla (EM). Apesar de a pesquisa nessa área ser limitada, estudos acerca da natureza dessa associação têm se concentrado em aspectos genéticos, reações adversas a drogas e lesões desmielinizantes no sistema nervoso central. Relatamos, aqui, três casos de pacientes com EM que também apresentaram transtorno bipolar do humor. A coexistência de sintomas neurológicos e psiquiátricos em grande parte das recaídas de EM reforça a importância de fatores biológicos na gênese dos sintomas afetivos nesses pacientes.